Simulation and synthesis in medical imaging : third International Workshop, SASHIMI 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 16, 2018, Proceedings /: third International Workshop, SASHIMI 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 16, 2018, Proceedings. (2018) - Unknown
No abstract available